2012
DOI: 10.1002/chem.201103710
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Approach Towards the Understanding of Asymmetric Additions of Dialkylzinc to Enals and Iminals Catalysed by [2.2]Paracyclophane‐Based N,O‐Ligands

Abstract: The 1,2- and 1,4-asymmetric additions of dialkylzinc reagents (ZnMe(2) and ZnEt(2)) to cinnamaldehyde and N-formylbenzylimine catalysed by [2.2]paracyclophane-based N,O-ligands were studied with quantum chemical methods. High level LPNO-CEPA/1 (local pair natural orbital coupled electron pair approximation 1) calculations were performed to obtain reliable reaction barriers and binding energies. The calculations supported the experimentally observed selectivities. In the reaction, the alkyl transfer takes place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…Conveniently, there is no special computer code required to perform activation strain analyses: all necessary quantities can be computed using any of the regular quantum‐chemical software packages available. As a result, the activation strain model has been applied by various research groups, on a range of chemical processes, such as nucleophilic substitution, cycloaddition, oxidative addition, isomerization, and many other processes from organic and organometallic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Conveniently, there is no special computer code required to perform activation strain analyses: all necessary quantities can be computed using any of the regular quantum‐chemical software packages available. As a result, the activation strain model has been applied by various research groups, on a range of chemical processes, such as nucleophilic substitution, cycloaddition, oxidative addition, isomerization, and many other processes from organic and organometallic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations, for example, by Noyori and Soai,9,10 showed that catalysis with [2.2]paracyclophane zinc complexes having a nitrogen–oxygen coordination motif is feasible. In recent years, we combined the rigidity of the [2.2]paracyclophane backbone with novel metal coordinating moieties and described the asymmetric conjugate addition (ACA) of diethylzinc to cinnamaldehyde utilizing different [2.2]paracyclophane ligands 1113. In this publication we present a series of new [2.2]paracyclophane derivatives bearing N‐heterocycles with various substitution patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the PNO-based approaches are developed in number of groups including Werner [87][88][89][90] and Hättig [91][92][93] and widely applied to various systems of chemical interest [94][95][96][97][98][99][100][101][102][103] . Apart from single-reference methods, the LPNO and DLPNO methodologies were also successfully applied to multireference CC techniques [104][105][106][107]…”
Section: Introductionmentioning
confidence: 99%